Conferenza AM/FM 2008 Una vetrina sullo stato dell'arte della tecnologia GIS (GEOmedia, 2008)
AM/FM Conference 2008: a showcase for state of the art GIS technologySeptember is highlighted by the AM/FM GIS annual conference held in Italy. AM/FM is a non-profit organization born to promote the sharing of knowledge in the GIS and geographic information sectors between public and private users. This year's conference underlined the importance of the research industry. The audience was provided with up-to-date information concerning the european industry with particular reference to the INSPIRE and eSDI-NET+ programs.